2012
DOI: 10.1093/nar/gks623
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of hepatitis C virus NS3 helicase inhibitors using nucleic acid binding assays

Abstract: Typical assays used to discover and analyze small molecules that inhibit the hepatitis C virus (HCV) NS3 helicase yield few hits and are often confounded by compound interference. Oligonucleotide binding assays are examined here as an alternative. After comparing fluorescence polarization (FP), homogeneous time-resolved fluorescence (HTRF®; Cisbio) and AlphaScreen® (Perkin Elmer) assays, an FP-based assay was chosen to screen Sigma’s Library of Pharmacologically Active Compounds (LOPAC) for compounds that inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 57 publications
9
73
0
1
Order By: Relevance
“…Among the resulting ligands, Suramin showed highest affinity for SFTSV-N. Suramin is a drug used for the treatment of trypanosomiasis and helminthiasis (37,38). Recently, its potential as an antineoplastic agent in the treatment of cancers and as an antiviral agent is being evaluated (39)(40)(41). Interestingly, while Suramin could bind SFTSV-N homologs such as RVFV-N (42), GRAV-N, and BUEV-N, it did not bind the Ns from other genera of the Bunyaviridae family (Orthobunyavirus, Nairovirus, and Hantavirus) or other viruses In the Suramin-bound structure of SFTSV-N, Suramin is found in the cavity encircling the central hole of the ring-like assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Among the resulting ligands, Suramin showed highest affinity for SFTSV-N. Suramin is a drug used for the treatment of trypanosomiasis and helminthiasis (37,38). Recently, its potential as an antineoplastic agent in the treatment of cancers and as an antiviral agent is being evaluated (39)(40)(41). Interestingly, while Suramin could bind SFTSV-N homologs such as RVFV-N (42), GRAV-N, and BUEV-N, it did not bind the Ns from other genera of the Bunyaviridae family (Orthobunyavirus, Nairovirus, and Hantavirus) or other viruses In the Suramin-bound structure of SFTSV-N, Suramin is found in the cavity encircling the central hole of the ring-like assembly.…”
Section: Discussionmentioning
confidence: 99%
“…1A). All ATPase assays in this screen were performed in the absence of RNA (or DNA) because primuline derivatives are known to prevent NS3 from binding nucleic acids (10). RNA stimulates helicase-catalyzed ATP hydrolysis, and any compound that prevents RNA from binding NS3h would inhibit ATP hydrolysis in the presence of RNA.…”
Section: Identification Of Hcv Helicase Inhibitors That Stimulatementioning
confidence: 99%
“…Primuline is a fluorescent dye composed of a mixture of benzothiazole oligomers terminating with p-aminobenzene groups, and it prevents proteins from binding ssDNA or RNA (1,10). Li et al synthesized a series of chemical derivatives from a benzothiazole dimer purified from primuline, and they showed that some of these compounds potently and specifically inhibit HCV helicase (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suramin has also been shown to block the binding or early steps of infection of several DNA and RNA viruses, like herpes simplex virus type-1 (Aguilar et al, 1999), cytomegalovirus (Baba et al, 1993), human hepatitis B virus (Schulze et al, 2007), hepatitis delta virus (Petcu et al, 1988), hepatitis C virus (Garson et al, 1999), dengue virus (Chen et al, 1997), several bunyaviruses (Crance et al, 1997;Ellenbecker et al, 2014;Iqbal et al, 2000;Jiao et al, 2013), norovirus-like particles (Tamura et al, 2004) and enterovirus 71 (Wang et al, 2014), for which the antiviral activity of suramin was also confirmed in an animal model (Ren et al, 2014). In recent in vitro studies suramin was identified as a hepatis C virus and dengue virus helicase inhibitor (Basavannacharya and Vasudevan, 2014;Mukherjee et al, 2012) and also as a norovirus RdRp inhibitor by virtual screening and biochemical assays with purified enzymes (Mastrangelo et al, 2012;Tarantino et al, 2014). In the present study we assessed the effect of suramin on CHIKV RNA synthesis using our recently established in vitro assay that relies on RTCs isolated from infected cells (Albulescu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%